The Questions Technique in Guided Paragraph Writing - Maharaj, Ameerchund; Alsolami, Turki (International Journal of Emerging Trends in Social Sciences, 2018)
Writing has always been an onerous task for ESL learners, especially those in the beginner - and elementary phases of English language acquisition. Teaching ESL writing has always been viewed and implemented using the L1 framework. This may account for the frustrations experienced by both teacher and students in ESL classes. New techniques and strategies have to be devised taking into account the unique circumstances of ESL learners. Using an experimental design, this study compared the number of writing errors made in a control and experimental group. The control group was taught paragraph writing in the conventional way incorporating elements of the product and process approaches to writing. The experimental group was given a pre-arranged set of questions to which they had to respond in a specific manner. It was found that the number of errors committed by the experimental group were significantly lower than the control group, thus suggesting that the Questions technique does have merit in teaching writing to ESL learners. It is versatile in the sense that it can be adapted for different ability levels and types of paragraphs.